2018
DOI: 10.18632/oncotarget.25585
|View full text |Cite
|
Sign up to set email alerts
|

Numb has distinct function in lung adenocarcinoma and squamous cell carcinoma

Abstract: Some reports suggest that Numb is a potential tumor suppressor. However, its role in non-small cell lung cancer remains unclear. Non-small cell lung cancer comprises two major histological subtypes, adenocarcinoma and squamous cell carcinoma. To investigate the role of Numb in tumorigenesis of lung adenocarcinoma and squamous cell carcinoma, we firstly performed loss-of-function and gain-of-function assays. Moreover, Numb expression was investigated in surgically resected lung adenocarcinoma and squamous cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…With respect to the Numb family, Kikuchi et al demonstrated that NUMB has the opposite role in both types of NSCLC. In LUAD, specifically, this leads to inhibition of tumor proliferation, migration and invasion, whereas in LUSC, it activates these processes [114]. Contrary to this, our OS analysis showed that both LUAD and LUSC have common trends, wherein lower expression of NUMB is favored (Table 3).…”
Section: Signaling Of the Core Components-modulatorscontrasting
confidence: 60%
“…With respect to the Numb family, Kikuchi et al demonstrated that NUMB has the opposite role in both types of NSCLC. In LUAD, specifically, this leads to inhibition of tumor proliferation, migration and invasion, whereas in LUSC, it activates these processes [114]. Contrary to this, our OS analysis showed that both LUAD and LUSC have common trends, wherein lower expression of NUMB is favored (Table 3).…”
Section: Signaling Of the Core Components-modulatorscontrasting
confidence: 60%
“…However, the same gene may play different or even contrary roles in different lung cancer subtypes. For instance, in lung adenocarcinoma, Numb protein impairs tumor growth and inhibits the Notch pathway and epithelialmesenchymal transition, whereas in lung squamous cell carcinoma, it may promote proliferation (25). In addition, we noticed that some mutant genes significantly influenced the metastasis/recurrence outcomes, especially ATM.…”
Section: Discussionmentioning
confidence: 88%
“…However, Numb may have promoter function in some cancers and a suppressor function in others. For example, Numb overexpression inhibits tumor growth and the epithelial-mesenchymal transition in prostate carcinoma, esophageal squamous cell carcinoma, adenocarcinoma of the lung, and breast cancer[ 43 , 44 ], but it promotes cell proliferation in hepatocellular carcinoma and squamous cell carcinoma of the lung[ 45 ]. Therefore, the influence of Numb in oncogenesis might be related to the type of malignancy or the histological subtype.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that Numb expression is higher in well-differentiated tumors, at earlier stages, and in patients without lymph node metastases, in contrast to the findings for Notch-1. Numerous experimental studies have shown that Numb protein expression is associated with cell differentiation in both normal tissues and tumors, concluding that it is a determinant of cell fate[ 41 - 44 ]. Similar findings have been obtained in experimental studies involving CRC cell culture.…”
Section: Discussionmentioning
confidence: 99%